Presence of foliar diseases caused by fungi in mangroves on the East Coast of Peninsular Malaysia - Sahibu A.; Siti Nordahliawate M.S.S.; Abdullah M.M. (Penerbit Universiti Kebangsaan Malaysia, 2020)
Mangrove health is very important for the ecosystem to survive the challenges and threats due to climate change and anthropogenic pressures. However, unhealthy mangroves due to pathogenic fungi causing diseases may demote the survival rate of younger plants to grow and information on the status of foliar disease incidence is limited. This study aimed 1) to observe the foliar disease symptoms that occurred on Rhizophora apiculata and Avicennia marina and 2) to identify the fungi isolated from the symptomatic leaves. Samples were collected from the mangrove area located in Universiti Malaysia Terengganu (UMT) campus, along the South China Sea. All isolates were identified based on their morphological characteristics. A total of five foliar disease symptoms were observed namely black leaf spot, grey leaf spot, leaf rot, sunken leaf blight, and anthracnose. Rhizophora apiculata has a greater number of leaf spots than A. marina. Four genera of fungi; Pestalotiopsis sp., Curvularia sp., Colletotrichum sp. and Rhizopus sp. were successfully isolated from symptomatic leaves where the most dominant was Pestalotiopsis sp. to both mangrove species. This finding g highlights the need to obtain the status of foliar diseases and their impact on the resilience of mangroves in Malaysia.